Use of Ameliorant to Reduce Methane and Carbon Dioxide Emissions from Rice Paddy at Peat Soils of Central Kalimantan - MULJADY D. MARIO (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2003)
Peat forests emit methane and carbon dioxide naturally. Rate of the emissions may increase if the forest is converted for other uses such as rice field. The use of mineral soil, enriched with electric furnace slag containing high level of cationic irons, as ameliorant is expected to give several benefits. Firstly, it can reduce the harmful effects of phenolic acids in the soils thereby increasing yield of rice. Secondly, it will form complex bonding that improves peat stability and reduces methane (CH4) andcarbon dioxide (CO2) emissions. This study evaluated the impact of using ameliorant in three peat soils of Central Kalimantan, i.e. inland peat at Berengbengkel, transitional peat at Sampit, and coastal peat at Samuda. The ameliorant was a combination of Ferich mineral soil (Fe2O3 =22.06%) and electric furnace slag (Fe2O3 =42.60%). The amount of ameliorant was determined based on 5% maximum adsorption of Fe3+. It was found thatinland peat soils emit more CH4 and CO2 than transitional and coastal peat soils. The use of ameliorant reduced the rate of the emission significantly. Without amelioration, total amount of carbon losses through CH4 and CO2 emission were about 2.086, 1.986, and 1.967 t ha-1yr-1 for inland, transitional, and coastal peats, respectively. Ameliorant application reduced total carbon losses in these three peat soils by about 0.597, 0.609, and 0.628 t ha-1yr-1, respectively, and also significantly the yield of rice. Based on the findings and if there was no ameliorant application, it is estimated to require 660, 1247, and 2820 years to decompose all organic carbon of inland, transitional, and coastal peat soils, respectively. Meanwhile, with ameliorant application, the time required will be about 980,1789, and 3950 years, respectively.